Diagnostic and prognostic significance of alpha-defensin in patients with chronic heart failure during 2-year follow-up - Joanna Banach; Łukasz Wołowiec; Daniel Rogowicz; Wojciech Gilewski; Katarzyna Buszko; Danuta Karasek; Piotr Małyszka; Walery Zukow; Władysław Sinkiewicz (Kazimierz Wielki University, 2018)
Background Defensins play an important role in the processes associated with innate immunity. Their growth is observed in sites of intense inflammation, but also in less severe inflammation. Evaluation of alpha-defensin levels in patients with chronic heart failure (CHF) and its possible association with a long-term prognosis may be an interesting supplement to knowledge about the state of the immune system in heart failure. The aim of the study was to compare the plasma concentration of alpha-defensin between the patients with chronic heart failure with impaired ventricular ejection fraction (LVEF)